HOW TO TEACH INCURABLE SEXUALLY TRANSMITTED INFECTIONS TO UNDERGRADUATE NURSING STUDENTS: A SCOPING REVIEW - Petry, Stéfany; Padilha, Maria Itayra; Mazera, Maiara Suelen; Silva, Amina Regina (Cogitare Enfermagem, 2023)
Objective: to group and synthesize the studies that address the teaching of Incurable Sexually Transmitted Infections for undergraduate Nursing students in the world (1989-2020). Method: a scoping review according to the Joanna Briggs Institute. The search strategy was carried out in PubMed, CINAHL, Embase, Web of Science and LILACS. Two reviewers selected and extracted the data independently. Results: after searching and removing duplicates, 41 studies met the established criteria and were included. Content analysis resulted in three categories: Teaching Scenarios and Strategies; Teaching Focus; and Teaching Effectiveness. Final considerations: the educational actions were effective in increasing knowledge, reducing stigma and anxiety, and increasing sensitivity in promoting Nursing care. Teaching this theme is important in the profession's work on epidemiological indices and in the training of Nursing students for prevention and promotion in health.